Dynamic Modeling and Flexibility Analysis of an Integrated Electrical and Thermal Energy System With the Heat Pump–Thermal Storage - Hao, Junhong; Gou, Xing; Wang, Shunjiang; Chen, Qun; Gao, Kai (Frontiers in Energy Research, 2022)
The integration of high-efficiency heat pump and thermal storage devices is of great significance to realize the synergy between efficient and flexible operation of the integrated electric and thermal energy systems. This article proposed an integrated electric–thermal energy system with heat pump and thermal storage devices and introduced the heat current method for constructing its overall dynamic power flow model by considering energy transfer, conversion, and storage processes. On this basis, we derived the overall system constraint and component constraint equations. Under the objective of wind power curtailment minimization, the comprehensive effects of the dynamic characteristics of the heat pump, thermal storage capacity, new wind power installation, and new heat load on the electric and thermal output are analyzed. The results show that the dispatching accuracy of wind power output can be improved by up to 8% by taking into account the dynamic characteristics of the heat pump. The combination of heat pump and thermal storage device results in a leverage factor of 3.06 and 0.17 for the storage and release processes, respectively, effectively increasing the flexibility of system scheduling. The coordination between the newly added wind power installation and the added new heat load, with the higher operating temperature of the heat pump, is more conducive to promote wind power accommodation and improve the system’s overall flexibility. These results provide the necessary basis for the development of an integrated dispatch plan for the integrated electric and thermal energy systems containing the heat pump–thermal storage.